A study on the development of data technology taxonomy for data economy - Hwasun You; Do-Bum Chung; Jangwon Choi; Heeseok Choi (PLoS ONE, 2025)
As the data economy era is in full swing, the impact of data is accelerating across the economy and society. In particular, as digital transformation accelerates, data technology is becoming more important, and new products and services are being created based on data. However, despite the increasing importance of data, the lack of a comprehensive taxonomy for data technology has resulted in inadequate systematic policy development and execution. Therefore, this study proposes a data technology taxonomy that can be used for data technology-related policy making, business planning, and national R&D investment direction setting. To this end, the study defines the concept of data technology that has not been officially announced, and develops a classification system while establishing the validity of the classification system through the derivation of the limitations of similar taxonomy and the collection of expert opinions. In addition, an expert adequacy assessment will be conducted to verify whether the proposed taxonomy can be used in the field, and the current status will be analyzed by classifying the data technology-related national R&D projects based on the taxonomy. The results of this study are meaningful in helping to understand data technology and improving the system in the future when formulating data policies and conducting research and development.